2012
DOI: 10.1017/s0265051712000083
|View full text |Cite
|
Sign up to set email alerts
|

Singing in primary schools: case studies of good practice in whole class vocal tuition

Abstract: Within the context of British initiatives in music education such as the Wider Opportunities programme in England and the recommendations of the Music Manifesto emphasising the importance of singing in primary schools, the current paper explores examples of good practice in whole-class vocal tuition. The research included seven different primary schools in England and combined observational methods and semi-structured interviews with musicians, teachers and headteachers. Results indicate a variety of successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Similarly, Swain and Bodkin-Allen (2017) showed that "gaining some knowledge of singing techniques [leads] to a sense of empowerment" in early childhood teachers (109). Research has shown that music mentoring by music specialists helps teachers acquire discipline-specific knowledge and teaching strategies (Draves and Koops 2011;Schmidt 2008) and builds their confidence (Davis 2016;Lamont et al 2012).…”
Section: Outcomes For Mentors Teachers and Studentsmentioning
confidence: 99%
“…Similarly, Swain and Bodkin-Allen (2017) showed that "gaining some knowledge of singing techniques [leads] to a sense of empowerment" in early childhood teachers (109). Research has shown that music mentoring by music specialists helps teachers acquire discipline-specific knowledge and teaching strategies (Draves and Koops 2011;Schmidt 2008) and builds their confidence (Davis 2016;Lamont et al 2012).…”
Section: Outcomes For Mentors Teachers and Studentsmentioning
confidence: 99%
“…Singing is an activity that has always been present in music teaching because singing is the most elemental, spontaneous, and natural way of expressing a person in music. As such, singing has given an important mark in the history of music teaching, and good experiences through singing in school are essential for a lifelong interest in music (Lamont et al, 2012;Pitts, 2009;Radočaj-Jerković, 2017;Spruce, 2002;Vidulin, & Terzić, 2011).…”
Section: Singingmentioning
confidence: 99%
“…Alongside learning to play an instrument, WCET programmes draw on a range of other music learning and performing activities, including clapping and rhythm games, movement, composing and listening to music. An important component of WCET programmes is singing, with the majority of programmes involving singing in some form (Lamont, Daubney, & Spruce, 2012). Some WCET programmes also involve learning to read from music notation, either staff notation, or graphic notation, or other forms.…”
Section: Wcet Contentmentioning
confidence: 99%